2002
DOI: 10.1093/ajcn/76.6.1230
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of diacylglycerol oil as part of a reduced-energy diet enhances loss of body weight and fat in comparison with consumption of a triacylglycerol control oil

Abstract: Foods containing diacylglycerol oil promoted weight loss and body fat reduction and may be useful as an adjunct to diet therapy in the management of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
136
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(153 citation statements)
references
References 21 publications
9
136
0
4
Order By: Relevance
“…The intake of certain beverages and functional foods has been shown to be effective at the suppression or reduction of body fat accumulation (Maki et al, 2002;Nosaka et al, 2003;Ikeda et al, 2005). Rats who were fed CBE, which contains 10.0% caffeine and 27.0% chlorogenic acid as the principal constituents, showed suppressed body weight gain irrespective of food and energy intake compared to those fed the control diet not containing CBE (CBE group: 82.3 ± 3.6 kcal/day; control group: 86.8 ± 2.0 kcal/day).…”
Section: Discussionmentioning
confidence: 99%
“…The intake of certain beverages and functional foods has been shown to be effective at the suppression or reduction of body fat accumulation (Maki et al, 2002;Nosaka et al, 2003;Ikeda et al, 2005). Rats who were fed CBE, which contains 10.0% caffeine and 27.0% chlorogenic acid as the principal constituents, showed suppressed body weight gain irrespective of food and energy intake compared to those fed the control diet not containing CBE (CBE group: 82.3 ± 3.6 kcal/day; control group: 86.8 ± 2.0 kcal/day).…”
Section: Discussionmentioning
confidence: 99%
“…11 Human studies in the US and Japan have demonstrated that long-term consumption of a diet containing DAG oil enhances loss of body weight and BF compared with a TAG oil with a similar fatty acid composition. 12,13 Animal studies have shown that both b-oxidation and expression of lipid metabolism-related genes in the liver and small intestine are enhanced with chronic DAG oil ingestion compared with TAG oil ingestion. [14][15][16] Several human studies have shown greater fat oxidation and/or lower respiratory quotient with short-term DAG oil consumption (single meal, 17 1 8 and 4 days 18 ) compared with TAG oil consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to determine whether repeated DAG oil consumption affects energy metabolism in overweight patients in a 14-day controlled feeding study. Simultaneously, we explored the effect of DAG oil consumption on dietary fat oxidation, as determined by the recovery rate of 13 C-stable isotope in the breath.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations